2015
DOI: 10.1007/s40097-015-0173-y
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of gold nanoparticles using marine algae and evaluation of their catalytic activity

Abstract: The hazardous effects of current nanoparticle synthesis methods have steered researchers to focus on developing newer eco-friendly methods for synthesizing nanoparticles using non-toxic chemicals. Owing to the diverse applications of nanoparticles in various fields such as catalysis, medicine, diagnostics, and sensors, several novel green approaches have been explored for synthesizing nanoparticles using different natural sources such as plants, algae, bacteria, and fungi. Hence, in the present work, a green m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(69 citation statements)
references
References 46 publications
(51 reference statements)
6
62
0
1
Order By: Relevance
“…Ramakrishna et al studied the synthesis of gold nanoparticles using aqueous extracts of brown algae, Sargassum tenerrimum and Turbinaria conoides. 90 The AuNPs displayed excellent biocatalytic activity in the degradation of aromatic nitro compounds and organic dyes. The metal nanoparticles of zinc oxide (ZnO) have also generated curiosity among researchers due to their unique physicochemical characteristics and wide applications in opto-electronics, sunscreens, biomedicine and food additives etc.…”
Section: Algaementioning
confidence: 99%
“…Ramakrishna et al studied the synthesis of gold nanoparticles using aqueous extracts of brown algae, Sargassum tenerrimum and Turbinaria conoides. 90 The AuNPs displayed excellent biocatalytic activity in the degradation of aromatic nitro compounds and organic dyes. The metal nanoparticles of zinc oxide (ZnO) have also generated curiosity among researchers due to their unique physicochemical characteristics and wide applications in opto-electronics, sunscreens, biomedicine and food additives etc.…”
Section: Algaementioning
confidence: 99%
“…Gold nanoparticles are widely used for medical applications such as diagnostics, therapy, prevention and hygiene [3]. AuNPs synthesized from microorganisms [4], algae [5], fungi [5], and plant materials [6,7] have been reported. There are several methods for the synthesis of diverse nanoparticles, such as physical and chemical as well as biological methods.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover it eradicates the complicated procedure of preserving microbial cultures and could also be stretched to bulk-scale production. Previous literature revealed that terrestrial plants have been extensively utilized for the preparation of metal nanoparticles [7][8][9][10][11][12] and only a limited number of reports on nanogold synthesis using renewable marine resources like marine macroalgae (seaweeds) [13,14]. Due to the richness of bioactive metabolites, marine macroalgae are promising source for both industrial and biotechnological applications.…”
Section: Introductionmentioning
confidence: 99%